Contrast of artificial subcutaneous hematomas in MRI over time - Hassler, Eva Maria; Ogris, Kathrin; Petrovic, Andreas; Neumayer, Bernhard; Widek, Thomas; Yen, Kathrin; Scheurer, Eva (International journal of legal medicine, 2015)
In clinical forensic medicine, hematomas and other externally visible injuries build the basis for the reconstruction of events. However, dating of subcutaneous hematomas based on their external aspect is difficult. Magnetic resonance imaging (MRI) has proven its use in dating intracranial hemorrhage. Thus, the aim was to investigate if MRI can also be used for dating subcutaneous hematomas and to analyze an eventual influence of the hematoma shape. In 20 healthy volunteers (11 females, 9 males, aged 26.9 ± 3.8 years), 4 ml of autologous blood were injected subcutaneously in the thigh. The hematoma was scanned immediately after the injection, after 3 and 24 h and 3, 7, and 14 days using three sequences with different contrast. Data was analyzed by measuring signal intensities of the hematoma, the muscle, and the subcutaneous tissue over time, and the Michelson contrast coefficients between the tissues were calculated. In the analysis, hematoma shape was considered. Signal intensity of blood in the proton density-weighted sequence reached its maximum 3 h after the injection with a subsequent decrease, whereas the signal intensities of muscle and fatty tissue remained constant. The time course of the Michelson coefficient of blood versus muscle decreased exponentially with a change from hyperintensity to hypointensity at 116.9 h, depending on hematoma shape. In the other sequences, either variability was large or contrast coefficients stayed constant over time. The observed change of contrast of blood versus muscle permits a quick estimate of a hematoma’s age. The consideration of the hematoma shape is expected to further enhance dating using MRI.